Hubungan Komitmen Tugas dan Prestasi Akademik Siswa Sekolah Menengah Pertama (SMP) Ditinjau Berdasarkan Jenis Kelamin atau Gender - Sutanto, Nadia; Murwani, Fulgentius Danardana; Hitipeuw, Imanuel (Faculty of Psychology, Universitas Surabaya, 2024)
Academic achievement is important for students and its achievement is influenced by various factors. One of them is task commitment. Task commitment is generally measured in gifted students. However, the authors believe that all students require commitment in the learning process and achieving academic achievement. This study aims to determine the differences in sex or gender perspectives in task commitment and academic achievement of Junior High School students in Indonesia, utilizing a cross-sectional research method on Grade 7 and Grade 8 students (N = 403). Measurement of task commitment utilizes an instrument developed by Sánchez-Escobedo. The results of the study showed no relationship between academic achievement and task commitment in general (r = .040; p = .418). However, there were interesting results related to perseverance as a single aspect (r = .130; p = .009), because it had a relationship with academic achievement in total and in Mathematics, Science subjects, and the results of regression analysis in male students (F = 3.083; p = 0.017). The results of the study also showed that there was a difference in academic achievement between male and female students (t(count) = 3.741; p = .000), but there was no significant difference in task commitment (t(count) = 0.557; p = .578). In this study, perseverance had a more significant relationship with academic achievement. The difference in academic achievement between male and female students indicates that there is something related to sex or gender that still needs to be studied further, in addition to task commitment.